In Silico Analysis of the Genomic Potential for the Production of Specialized Metabolites of Ten Strains of the Bacillales Order Isolated from the Soil of the Federal District, Brazil - Mesquita, Felipe de Araújo; Mendes Cordeiro da Silva, Waldeyr; De-Souza, Marlene Teixeira (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2022: Anais do XV Simpósio Brasileiro de Bioinformática, 2022)
Secondary or specialized metabolites play an important ecological role for the producing organisms. Bacteria isolated from soils are a major source of specialized metabolites. Species of Bacillus and related genera, collectively referred to as aerobic endospore-forming bacteria (AEFB), produce specialized metabolites with high structural and functional diversity. In this study, ten genomes of AEFB strains isolated from the soil of Federal District, Brazil, were scanned for specialized metabolism genes. Using the antiSMASH 6.0 bacterial standalone version, we identified 153 putative gene clusters codifying for specialized metabolite synthesis in these ten strains. Such clusters encode, for example, enzymes for bacillibactin, bacillisin, macrolactin H, bacilliaene, paenibacterin, nostamid A and macrobervin, revealing pathways 100% similar to the genomic information available in the antiSMASH database. The results suggest that AEFB are promising for exploring known and unknown specialized metabolites, notably antimicrobial agents.